2013
DOI: 10.1097/jom.0b013e3182898639
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Technology in a Workplace Wellness Program With Health Risk Factor Reduction

Abstract: Engaging technology and interactive Web-based tools can empower individuals to be more proactive about their health and reduce their health risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The HWCE provided collaboration on the design of the previous questionnaire and contracted with DPLB to administer the current ETHM-based questionnaire, which used the same format and many of the same items included in previous DPLB surveys (see Table 3 for the full questionnaire). Survey data included employment sector, organization size, rural or urban location as defined by USDA Rural-Urban Continuum Codes 11 , insurance coverage, and health and wellness module responses. All analyses were conducted at the HWCE using SAS, version 9.2 (SAS Institute, Inc., Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
“…The HWCE provided collaboration on the design of the previous questionnaire and contracted with DPLB to administer the current ETHM-based questionnaire, which used the same format and many of the same items included in previous DPLB surveys (see Table 3 for the full questionnaire). Survey data included employment sector, organization size, rural or urban location as defined by USDA Rural-Urban Continuum Codes 11 , insurance coverage, and health and wellness module responses. All analyses were conducted at the HWCE using SAS, version 9.2 (SAS Institute, Inc., Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that as participants increased their engagement in the program, there was a significant reduction in reported risk factors. The authors also documented a dose-response relationship between the number of times participants logged on to the program website and a reduction in risk factors (Loeppke et al, 2013). These results mirror findings of another meta-analysis that reported increased usage of a program's website was associated with positive weight change, suggesting that exposure to, and engagement in the webbased components of an intervention are critical to success (Eisen, Allen, Bollash, & Pescatello, 2008;Neve, Morgan, Jones, & Collins, 2010).…”
Section: Increasing Participation In Health Promotion Programs Previsupporting
confidence: 54%
“…The dose-response relationship between increased participation in face-to-face HPPs and improved outcomes has been previously outlined . To better understand the relationship between computer-based programs and participation, researchers reviewed engagement in The Prevention Plan across a sample of 7804 employees (Loeppke, Edington, Bender, & Reynolds, 2013). Participants were stratified into three different engagement levels, with the first group only completing a HRA, the second group also completing at least one virtual or social challenge in the program, and the third group consisting of participants who took advantage of live coaching.…”
Section: Increasing Participation In Health Promotion Programs Previmentioning
confidence: 99%
See 1 more Smart Citation
“…8 One recent program evaluation showed increased engagement (i.e., live coaching or virtual programming paired with an HRA, compared to simply completing an HRA) was also related to improved clinical outcomes. 9 The relationship between increased engagement and increased effect has also been replicated for web-based programming, with one study finding that participants who logged on to the intervention site more frequently were more likely to lose weight than those with lower usage. 10 Some programs have reported success by providing tailored choices for wellness programming that allow employees to experience a sense of control over their health behaviors.…”
Section: Introductionmentioning
confidence: 94%